Outcomes of Bone Grafting of Bone Cysts After Total Ankle Arthroplasty. (February 2016) - Gross, Christopher E.; Huh, Jeannie; Green, Cynthia; Shah, Samit; DeOrio, James K.; Easley, Mark; Nunley, James A.
Background: The operative treatment of bone cysts after total ankle replacements (TAR) is not well described. Bone cysts may cause component migration, implant failure, and pain. Surgery is performed on cysts with the goals of reducing pain and preventing component failure. Methods: We retrospectively evaluated a consecutive series of 726 primary TARs performed between January 1998 and May 2013 and identified those who had a subsequent bone cyst grafting procedure. We identified cyst location and method of treatment. Clinical outcomes including secondary procedures, infection rate, complications, and failure rate were recorded. Thirty-one patients were treated with a total of 33 operative procedures for bone cysts after TAR. Of these patients, 22 (71.0%) were males with an average age of 62.2 and median follow-up 65.9 months. Results: Intraoperatively, 22 tibial cysts (71.0%), 20 talar cysts (64.5%), 5 fibular cysts (16.1%), and 13 multiple cysts (41.9%) were treated. Allograft was used in 25 procedures (75.8%), calcium phosphate in 4 (12.1%), cement in 3 (9.1%), and autograft in 1 (3.0%). These procedures were supplemented by calcaneus autograft, allograft mixed with mesenchymal stem cells, platelet-rich plasma, recombinant human bone morphogenic protein-2, and demineralized bone matrix. There were no infections or wound complications. Of the 27 subjects with a successful second surgery, the success rate for bone grafting of cysts was 90.9% (95% CI: 50.8, 98.7%) at 24 months and 60.6% (95% CI: 25.1%, 83.4%) at 48 months. One patient needed a repeat bone grafting. The 4 failures observed postprocedure resulted in 3 tibial and talar component revisions, and 1 tibiotalocalcaneal (TTC) fusion. Conclusions: Grafting bone cysts without revision of TAR was in general an effective and safe means for treating patients with peri-prosthetic bone cysts. Treatment with grafting and supplemental materials may improve implant survivorship and might improve the structural support surrounding the implant. Further exploration of the etiology of bone cysts may aid in the prevention and treatment of cystic formation in the TAR. Level of Evidence: Level IV, case series.